The Future of Jihadism in Europe : A Pessimistic View - Hegghammer, Thomas (Alex P Schmid, 2016)
This article presents a ten-year forecast for jihadism in Europe. Despite reaching historically high levels in recent years, violent Islamist activity in Europe may increase further over the long term due to four macro-trends: 1) expected growth in the number of economically underperforming Muslim youth, 2) expected growth in the number of available jihadi entrepreneurs, 3) persistent conflict in the Muslim world, and 4) continued operational freedom for clandestine actors on the Internet. Over the next decade, the jihady attack plot frecuency in Europe may follow a fluctuating curve with progressively higher peaks. Many things can undercut the trends and lead to a less ominous outcome, but the scenario is sufficiently likely to merit attention from policymakers.
Keywords: Terrorismo; Yihad; Prospectiva; Europa